"Dished like a dinner" by the Victorians? The 1899 Seat of Government Compact and its Repercussions in the early Australian Commonwealth. (29th January 2019) - Strangio, Paul
Abstract : At a "secret" conference in January‐February 1899, the premiers of the Australian colonies agreed on an amendment to the draft Commonwealth Constitution Bill to grant New South Wales the permanent seat of government in the Australian federation. One of the conditions placed on that concession, however, was that Melbourne would initially host the Commonwealth parliament. Spanning the decade from that agreement to the Commonwealth parliament's selection in 1908 of Canberra as the site for the permanent federal capital, this paper shows that the compact on the seat of government provoked powerful resentments in New South Wales and especially Sydney because of the political and material advantages it was seen to have conferred on Melbourne. While the paper argues that resentment was actuated by residual anti‐federal sentiment and regional chauvinism, it also suggests that hosting the legislature did promote Victoria's pre‐eminence in the early Commonwealth and had enduring effects on the nation. In doing so, it speaks to the shaping influence of place and distance in Australian history.